Evaluasi resep obat batuk anak di salah satu apotek - Reny Haryani; Lailatul Kasanah; Rastria Meilanda (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Prescription review is an evaluation of prescription writing conducted by pharmaceutical personnel, covering administrative, pharmaceutical, and clinical aspects. Prescription review is an important step in preventing medication errors. Purpose: to determine the appropriateness of prescriptions for children's cough medicine. Method: This study used a non-experimental design with a descriptive approach. The sampling technique was simple random sampling. Based on calculations using the Slovin formula, 96 prescriptions were obtained, which were then rounded up to 100 prescriptions as the research sample. Results: The study showed the completeness of administrative aspects included: patient name (100%), age (100%), gender (0%), weight (0%), doctor's name (100%), and doctor's SIP number (51%). In the pharmaceutical aspect, the results obtained were dosage strength (1%), route of administration (100%), and drug combination suitability (100%). Meanwhile, in the clinical aspect, the results were: drug interaction suitability (94%), drug dosage (88%), drug administration route and allergy history (100%), and contraindications (100%). Conclusion: Prescriptions for children's cough medicine for the period January–December 2022 generally complied with the standards set out in Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016.